Antimicrobial Activity of Essential Oil from Tagetes minuta L. and its Extracts along with its GC-MS Profiling - Adhikari, Sujata; Aryal, Sita (Journal of Plant Resources, 2025)
Nepal, being a land of diverse topography with the different weather conditions, is considered as storehouse of medicinal and aromatic plants (MAPs) with enriches medicinal values. Tagetes minuta L. is highly demanded aromatic plant for its essential oil, hugely used in flavor and perfumery industries, having potential bioactive and therapeutic properties. The essential oil was extracted from aerial parts of Tagetes minuta L. via hydro-distillation and its chemical composition was analyzed using GC-MS technique. Furthermore, the antimicrobial activity of oil and its hexane, ethylacetate, and methanolic extracts was assessed against different pathogenic bacterial strains using agar well diffusion method. The essential oil yield was 0.3% (v/w) and GC-MS data revealed the highest percentage of monoterpenes: alpha pinene (33.12 %), transocimenone (23.32 %), cistagetone (12.18%) and dihydrotagetone (9.65%) along with other hydrocarbons. Similarly, the antimicrobial activity showed ethylacetate and methanolic extracts to be quite active against pathogenic bacterial strains Staphylococcus aureus (ATCC 6538P) with Zones of Inhibition (ZOI) 14.30 mm and 10.40 mm and Staphylococcus epidermidis (ATCC 12228) with ZOI value of 17.50 mm and 16.30 mm respectively. On the other hand, it also showed moderate activity against pathogenic bacterial strains Bacillus subtilis (ATCC 8739) and Proteus vulgaris (ATCC 6380). Although additional necessary investigations are needed, these results support the use of traditional medicinal plants in treating various diseases. Also, these results suggest that the studied essential oil may have potential for isolating the bioactive compounds, which could contribute to the discovery of noble drugs in future.